Interactive Hadith Learning E-Module Integrated with Google Classroom in the Digital Era: A Literature Study - Syuhada, Dwi; Alindar, Dwi Putra; Anjani, Fariza; Hastuty, Ade (AR-RASYID : Jurnal Pendidikan Agama Islam, 2025)
This research aims to explore the design of interactive e-modules in Hadith learning connected to Google Classroom as part of the digital transformation in Islamic education. The method used is a literature study with a qualitative approach, which collects and analyzes various academic sources related to the development of digital learning media, the implementation of LMS, and interactive approaches in studying Hadith. The research results show that an effective Hadith e-module consists of five main sections: introduction, Hadith material, explanation, exercises, and evaluation. This module also includes various multimedia elements such as audio for reading Hadith, explanatory videos, and sanad graphics. Integrated into Google Classroom, this e-module facilitates structured material management, utilizes assignment and quiz features, and enhances interaction between lecturers and students. In addition, using online Hadith search sites such as Hadits Tazkia, Hadits.id, and Hadits.in also provides advantages in improving students’ digital and Islamic literacy. The research concludes that the development of interactive e-modules based on Google Classroom is an effective strategy to improve the quality of Hadith learning that is contextual, flexible, and participatory in the digital era.